3D porous carbon network-reinforced defective CoFeOx@C as a high-rate electrode for lithium-ion batteries. (1st October 2022) - Xue, Lichun; Li, Yueqing; Chen, Feiming; Lin, Wentao; Chen, Dengjie
Highlights: Three-dimensional porous carbon network-reinforced composites have been developed. The carbon-coated oxide (CoFeOx @C) was derived from the Prussian blue analogue. The CoFeOx @C/C electrode delivers excellent capacity and cyclability. The superior performance benefits from the interconnected structure. Abstract: Integrating metal oxides with three-dimensional (3D) porous carbon is extremely desirable for improving the capacity and cyclability of lithium-ion batteries (LIBs). Herein 3D porous carbon network (3DPCN)-reinforced composite electrodes were developed by integrating biomass (i.e., agaric)-derived 3DPCN and Prussian blue analogue (PBA)-generated carbon-coated metal oxides (CoFeOx @C). To achieve an integrated structure, PBA precursors were directly deposited and grown on 3DPCN (PBA/3DPCN), and then, PBA/3DPCN was subjected to low-temperature oxidation in air and thermal treatment in Ar to yield double carbon-modified metal oxides (CoFeOx @C/C). The interconnected CoFeOx @C/C electrode, as an advanced anode of LIBs, delivers excellent capacity and cyclability, with typical specific capacities of 1043.4 mAh  g −1 at 0.2 A  g −1 and 483.2 mAh  g −1 at as high as 5.0 A  g −1 after 120 cycles. This superior electrochemical performance originates from the interconnected structure of 3DPCN, the finely regulated composition of nanosized CoFeOx @C, and the tight contact and synergistic effect between 3DPCN and CoFeOx @C. The 3DPCN not only provides a void space for buffering the volume change of CoFeOx @C but also acts as a framework for improving the conductivity of the entire electrode, while compositionally optimized defective CoFeOx @C contributes the majority of the specific capacity. Our work paves the way to overcome the drawbacks (e.g., low electronic conductivity, self-aggregation, and low rate capability) of metal oxides as electrodes of LIBs. Graphical abstract: Image, graphical abstract